The Effect of Intellectual Capital Disclosure Disclosure on Financial Performance and Firm Value in Banking Companies Listed on the IDX: Pengaruh Pengungkapan Intellectual Capital Disclosure Terhadap Kinerja Keuangan dan Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar Di BEI - Ardiansyah, Ferdi; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2021)
Important information for investors in making investment decisions is reflected in the financial statements. Investors certainly expect a high rate of return from the funds invested in the company. The purpose of this study was to determine the effect of intellectual capital disclosure on financial performance and firm value in banking companies listed on the Indonesia Stock Exchange in 2015 – 2019. Through the criteria in the purposive sampling method, a sample of 14 banking companies was obtained. The panel data regression analysis technique is Partial Least Square (PLS) regression analysis. The panel data will be analyzed using Partial Least Square (PLS). And obtained the results that (1) Intellectual Capital Disclosure has an effect on Financial Performance, (2) Intellectual Capital Disclosure has an effect on Firm Value.